Hemangioma of the eyebrow. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
Both the first case treated with cortisone in 2003 and the second case treated with propranolol regressed very rapidly, demonstrating the sensitivity of hemangioma to both treatments. If we had seen the second case before 2008 we would certainly not have treated it. We use really beta-blockers nowadays even for significant esthetic reasons and their consequent psychological results. Regardless of the type of therapy, when hemangioma regresses a side effect linked to the eyebrow seat leads to widening of the eyebrow with more distanced hairs (1, 2). The widening can be treated by depilation. In adolescence, when the esthetic requirements increase, the rarefaction of hairs can be remedied by therapeutic tattoo. However, it is important to warn parents of this little known side effect of hemangioma located on the eyebrow.